Moyokoten Village Community Perspective on Online Marriage - Mohammad Yusuf Fitrian Nur Ihsan; Hafizh Hafiyyan; Choliliyah Thoha (UMSU, 2022)
Organizing weddings during the COVID-19 pandemic experience obstacles therefore adjustments were needed in the wedding ceremony. The development of increasingly sophisticated technology becomes the intermediary. One of them is to hold a marriage covenant online through a video call application. The purpose of this study is to find out how the PERSPECTIVE OF THE COMMUNITY OF MOYOKETEN VILLAGE, TULUNGAGUNG REGENCY toward online marriage. This research is expected to find the best way to organize weddings during the COVID-19 pandemic. This type of research is research that uses a qualitative method with a case study approach that aims to understand the community's perspective on marriages held online in Moyoketen Village. The results showed that the people of Moyoketen Village had various views and opinions on online marriage. It is suggested to the people of Moyoketen Village to get more information about marriage online.